20) Simplify: 3ab(4b-ab) + 5b2(a2 + 2)

Question

20) Simplify: 3ab(4b-ab) + 5b2(a2 + 2)

in progress 0
Hải Đăng 5 months 2021-09-05T10:31:51+00:00 2 Answers 2 views 0

Answers ( )

    0
    2021-09-05T10:33:07+00:00

    Answer:

    12ab^2+2a^2b^2+10b^2

    Step-by-step explanation:

    3ab(4b-ab) + 5b^2(a^2 + 2)\\\\\mathrm{Expand}\:3ab\left(4b-ab\right):\quad 12ab^2-3a^2b^2\\\\=12ab^2-3a^2b^2+5b^2\left(a^2+2\right)\\\\\mathrm{Expand}\:5b^2\left(a^2+2\right):\quad 5a^2b^2+10b^2\\\\=12ab^2-3a^2b^2+5a^2b^2+10b^2\\\\\mathrm{Add\:similar\:elements:}\:-3a^2b^2+5a^2b^2=2a^2b^2\\\\=12ab^2+2a^2b^2+10b^2

    0
    2021-09-05T10:33:24+00:00

    2a^2 b^2 + 12ab^2 + 10b^2

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )